Perspektif Human Rights Principles Dalam Penetapan Jabatan Fungsional Guru Sebagai Pegawai Pemerintah Dengan Perjanjian Kerja (PPPK) - Sahida Ayu Fajjari; Yati Sharfina Desiandri (Mahesa Research Center, 2024)
This research aims to discuss the importance of upholding human rights principles (HRP) in teacher profession policies, particularly regarding the appointment of Functional Teacher positions as PPPK civil servants. This study employs a juridical-normative method with a human rights-based approach to evaluate related policy regulations. The research findings indicate that the designation of the Functional Teacher Position as a PPPK civil servant violates HRP principles such as equality, interconnectedness, and non-discrimination. Therefore, a re-evaluation of this policy is necessary, considering HRP principles, and reinstating the status of the Functional Teacher Position as PNS civil servants in the SSCASN process. This research is descriptive, utilizing data from legislation, books, and scholarly articles related to HRP. Thus, understanding and respecting HRP principles are crucial in establishing teacher profession-related policies.